Decoding Customer Choices: Unraveling the Impact of Personality, Reputation, and Shariah Compliance on Financial Service Selection - Kharisma Putra, Gilang; Fitria Yuni, Astuti; Arum , Pujiastuti (JMIK: Jurnal Manajemen dan Inovasi Kewirausahaan, 2025)
This research investigates whether personality, reputation, and Sharia compliance influence customers' choices when using financial services in Kendal Regency. This study employs a quantitative research method to test the proposed hypothesis. The research population comprises all customers of Sharia-compliant banks in Kendal Regency. A purposive sampling approach was used to select a sample of 122 respondents for this study. The results show that reputation and sharia compliance positively related to customer choices. However, personality does not affect the customer choices. This research includes a broader range of respondents from all Shariah-compliant banks in Kendal, while prior research only focused on one specific bank branch. These results are expected to provide valuable insights for the banking industry, especially in the marketing department, to implement effective strategies to attract customers. In conclusion, the findings of this research shed light on the factors that can influence customers' decisions in Shariah banks and can serve as useful input for the banking industry in developing effective marketing strategies to attract customers.